KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KANTOR KELURAHAN KALI KECAMATAN BIAU KABUPATEN BUOL - Syahdan, Syahdan (Katalogis, 2018)
The purpose of this study was to determine The Quality of Administrative population service at Kali Village Office of Biau District in Buol Regency. The theory is used to measure the quality of service is a theory proposed by Taliziduhu Ndraha , dimensional quality of service includes speed, accuracy, easiness and equity. This research is classified as descriptive research. With a qualitative approach., This type of data consists of primary data and secondary data. Retrieval and data collection is done through observation, interview, documentation and triangulation. Data analysis was carried out by means of data collection, data presentation and inference. the results of this study show that service quality indicators of speed and accuracy showed unsatisfactory conditions while indicators accuracy and equity shows in quite satisfactory condition.